OPTIMALISASI MANAJEMEN DAKWAH DALAM MENGELOLA PERBEDAAN DAN MEMBANGUN PERSATUAN ORMAS ISLAM - Putri Sri Desti Anggraini; Ani Ainun Rodiah; Nia Nur Azlina; Khairina Firantinoor; Tiara Nur Sapira; Hana Rosdiana; Hani Amalia; Nabilah Noviyati; Nailah Noviyanti; Suciati Amalia; Muhammad Andri Maulana; Khoiru Roja; Feri Andika; Pandu Prasetya; Indra Bustaman; Fadel Ramadhan; Muhammad Naufal Azmi; Tb Nurwahyu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study discusses the optimization of da’wah management in managing differences and strengthening unity among Islamic community organizations in Indonesia. Differences in views, da’wah methods, and organizational backgrounds often become dynamics within the life of Muslim society. In the digital era, the development of social media and online communication platforms also influences the pattern of da’wah and the relationships among Islamic organizations. This study aims to examine the concept of da’wah management from an Islamic perspective, the dynamics of differences among Islamic organizations, da’wah communication strategies in managing differences, and the role of religious leaders in maintaining Muslim unity. The research method used is library research by analyzing various literature sources and a YouTube video from the Log In program episode entitled “ORMAS ISLAM BERSATU.” The results show that da’wah management carried out in a directed, communicative, and adaptive manner toward technological developments can strengthen Islamic brotherhood (ukhuwah Islamiyah). In addition, da’wah approaches that emphasize politeness, moderation, and dialogue are considered capable of reducing conflicts caused by differences in views among Islamic groups. Religious leaders also play an important role in creating a harmonious atmosphere through tolerance, exemplary attitudes, and calming communication. Therefore, the optimization of proper da’wah management is expected to maintain the unity of Muslims amid diversity